Performance evaluation of MODIS and VIIRS satellite AOD products over the Indian subcontinent - Payra, Swagata; Sharma, Ajay; Mishra, Manoj Kumar; Verma, Sunita (Frontiers in Environmental Science, 2023)
In the present study, a first systematic performance evaluation of aerosol optical depth (AOD) product retrieved from two satellite sensors i.e. Visible Infrared Imaging Radiometer Suite (VIIRS) and Aqua-Moderate Resolution Imaging Spectro radiometer (MODIS) is carried out over Indian region. We have used MODIS Aqua version C6.1(C061) dark blue (DB) aerosol product for inter-comparison with VIIRS/SNPP collection version-1.1 (V1.1). DB aerosol product and ground based AOD from AERONET at 550 nm wavelength over the time span of 6-year (2014-2020) observation periods. For the validation, average value of satellite pixels falling within the box of 50 Km x 50 Km keeping AERONET station at center are retrieved. Average daily data from AERONET sun photometer (2014 to 2019) was obtained within ±15 minutes of satellite overpass time. Calculation of statistical parameters like Correlation coefficient (R), RMSE, MAE, RMB, Precision (P) were performed. Evaluation of uncertainty of satellite AOD is performed using Expected Error Envelope (EE = ±0.05 + 0.15AOD, for land). Statistical analysis shows that MODIS AOD product outperforms VIIRS retrieved AOD. The AOD retrieved from both sensors yield high correlation (0.86-Jaipur and 0.79-Kanpur, 0.75-Jaipur and 0.77-Kanpur, for MODIS and VIIRS respectively) low MAE (0.12-Jaipur and 0.20-Kanpur, 0.13-Jaipur and 0.13-Kanpur, for MODIS and VIIRS respectively). Other statistical measures such as RMSE, RMB, P also suggest similar performance. More than 66% of total data fall within the range of EE for both the satellite product at each station. Spatial comparison exhibits the same AOD pattern seasonally as well as annually having a minimum bias of -0.3 to +0.3 between MODIS and VIIRS. Both satellites underestimate AOD value greater than 1, while values between 0.3 and 1 are overestimated where most of the data reside. Overall, the comparison of ground AERONET AOD reveals better accuracy of MODIS AOD with that of VIIRS satellite datasets over India